HIV status, knowledge, attitudes and behaviour of persons with and without disability in South Africa: Evidence from a national population-based survey - Supa Pengpid (2020)
© Supa Pengpid et al. Introduction: people with disabilities have been identified as a key risk population for HIV. The aim of this study was to investigate HIV status, knowledge, attitudes, behaviours and its correlates in persons with and without disabilities in South Africa. Methods: cross-sectional data of 26404 participants 15 years and older from the "2012 South African national HIV prevalence, incidence and behaviour survey” were analysed. Results: 1348(5.3%) had a disability. Persons with a disability were older (median age 52 years, IQR=24; versus 36 years, IQR=29), more often men, had a lower education and lower income and more likely living in a rural area than persons without disability. The prevalence of HIV infection was 16.7% in persons with disability, 23.0% in persons with visual/hearing or speech disability, 31.6% in persons with hearing disability and 16.2% in persons without disability. Antiretroviral (ARV) exposure in the HIV positive population was 41.3% among persons with disability and 30% in persons without disability. In multivariable logistic regression analysis, persons with disability had a lower odds to know an HIV testing site (Odds Ratio=OR: 0.46, Confidence Interval=CI: 0.22, 0.98) and a higher odds to have had two or more sexual partners in the past 12 months (OR 2.74, CI: 1.44, 5.21), had casual or transactional sex (OR: 6.25, CI: 2.57, 15.21) and psychological distress (OR: 2.10, CI: 1.50, 2.95) than persons without disability. In multivariable logistic regression analysis in both groups (with and without disability), psychological distress (OR: 2.90, CI: 1.53, 5.47, and OR: 1.90, CI: 1.20, 3.01, respectively) and high HIV stigma (OR: 0.31, CI: 0.25, 0.67, and OR: 0.57, CI: 0.34, 0.96, respectively) were associated with increased prevalence of HIV infection. Conclusion: the study found a high prevalence of HIV infection in persons with disabilities, in particular in those with hearing impairment. In some areas, persons with disability showed lower knowledge and higher risk behaviours than persons without disabilities. There is a need to strengthen HIV information and communication strategies geared towards targeting people with all types of disabilities.